Design of Rhenium Compounds in Targeted Anticancer Therapeutics - Collery, Philippe; Desmaele, Didier; Vijaykumar, Veena (Current Pharmaceutical Design, 2019)
Background: Many rhenium (Re) complexes with potential anticancer properties have been synthesized in the recent years with the aim to overcome the clinical limitations of platinum agents. Re(I) tricarbonyl complexes are the most common but Re compounds with higher oxidation states have also been investigated, as well as hetero-metallic complexes and Re-loaded self-assembling devices. Many of these compounds display promising cytotoxic and phototoxic properties against malignant cells but all Re compounds are still at the stage of preclinical studies. Methods: The present review focused on the rhenium based cancer drugs that were in preclinical and clinical trials were examined critically. The detailed targeted interactions and experimental evidences of Re compounds reported by the patentable and non-patentable research findings used to write this review. Results: In the present review, we described the most recent and promising rhenium compounds focusing on their potential mechanism of action including, phototoxicity, DNA binding, mitochondrial effects, oxidative stress regulation or enzyme inhibition. Many ligands have been described that modulating the lipophilicity, the luminescent properties, the cellular uptake, the biodistribution, and the cytotoxicity, the pharmacological and toxicological profile. Conclusion: Re-based anticancer drugs can also be used in targeted therapies by coupling to a variety of biologically relevant targeting molecules. On the other hand, combination with conventional cytotoxic molecules, such as doxorubicin, allowed to take into profit the targeting properties of Re for example toward mitochondria. Through the example of the diseleno-Re complex, we showed that the main target could be the oxidative status, with a down-stream regulation of signaling pathways, and further on selective cell death of cancer cells versus normal cells.
Keywords: personalized treatment